Performance Analysis of Hybrid PV/Diesel Energy System in Western Region of Saudi Arabia - Makbul A. M. Ramli; Ayong Hiendro; H. R. E. H. Bouchekara (International Journal of Photoenergy)
The potential implementation of hybrid photovoltaic (PV)/diesel energy system in western region of Saudi Arabia is analyzed in this paper. The solar radiation intensity considered in this study is in the range of 4.15–7.17 kWh/m2/day. The HOMER software is used to perform the technical and economical analysis of the system. Three different system configurations, namely, stand-alone diesel system, and hybrid PV/diesel system with and without battery storage element, will be evaluated and discussed. The analysis will be addressed to the impact of PV penetration and battery storage on energy production, cost of energy, number of operational hours of diesel generators, fuel savings, and reduction of carbon emission for the given configurations. The simulation results indicate that the energy cost of the hybrid PV/diesel/battery system with 15% PV penetration, battery storage of 186.96 MWh, and energy demand of 32,962 MWh/day is $0.117/kWh.